Analyses of the Compositions, Antioxidant Capacities, and Tyrosinase-Inhibitory Activities of Extracts from Two New Varieties of Chrysanthemum morifolium Ramat Using Four Solvents - Yen Hua Chen; Sheng Lei Yan; Jane Yii Wu; Chang Wei Hsieh; Sue Hong Wang; Ming Shiun Tsai (Applied Sciences, 2021)
Chrysanthemum morifolium Ramat is traditionally used as both medicine and food in China. In this study, extracts of C. morifolium Ramat Hang Ju No. 1 (No. 1) and No. 2 (No. 2) were produced using four different solvents: 95% ethanol, ethyl acetate, n-hexane and distilled water. In total, eight types of extracts were analyzed for extraction yields and total flavonoids, polyphenols, glycans, reducing sugars, and chlorogenic acids. The antioxidant capacities and tyrosinase-inhibitory activities of these extracts were also determined. Among them, the ethanolic extract of No. 1 (No. 1A) had the highest levels of total flavonoids (16.71 mg rutin equivalent/g dry weight (DW)), polyphenols (7.07 mg gallic acid equivalent/g DW), and chlorogenic acids (6595.46 μg/g DW) and the water extract of No. 1 (No. 1D) had the highest levels of total glycans (9.24 mg/g DW), and reducing sugars (23.32 μg/g DW). In terms of antioxidant capacity, No. 1A (1.0 mg/mL) demonstrated the best 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity (96.2 ± 0.4%), ferrous ion chelating ability (55.44 ± 0.03%), and reducing power (0.988 ± 0.003). No. 1D (1.0 mg/mL) showed the highest tyrosinase inhibitory activity (39.34 ± 0.03%). From these results, high levels of total flavonoids and polyphenols correlate with antioxidant capacity. Moreover, high levels of total chlorogenic acid in No. 1A and No. 1D correlate with high levels of tyrosinase inhibitory activity. Therefore, No. 1A has the potential to be used in daily health drinks, foods and skin whitening products. These results can be applied to similar flower plant extracts.